Developing consensus outcome measures in juvenile systemic sclerosis: a global survey of pediatric rheumatologists and literature review - Natalia Vasquez-Canizares; Clare E. Pain; Francesco Zulian; Amra Adrovic Yildiz; Simone Appenzeller; Edoardo Marrani; Emanuela Del Giudice; Antonella Petaccia; Francesca Tirelli; Gabriele Simonini; Mustafa Çakan; Marco Cattalini; et al. (Pediatric Rheumatology Online Journal, 2025)
Abstract Background Juvenile systemic sclerosis (JSSc) is a rare multisystemic disease with high morbidity and mortality rates. Treatment options remain limited, and there is a significant unmet need for effective therapies. This study aims to address this gap by investigating current JSSc management practices and identifying key outcome measures that can be used to inform the development of standardized assessment tools for future clinical trials. Methods A web-based survey was distributed to pediatric rheumatologists to assess cardiopulmonary assessment standard of care practices and immunosuppressive treatment use in JSSc. Respondents were categorized by region (North America, Europe, Latin America, and Asia/Africa), and country income level. A scoping literature review was conducted using the PRISMA-SCR framework to identify outcome measures for six domains in SSc. Results One hundred forty-one pediatric rheumatologists from 26 countries completed the survey. Significant variations in JSSc cardiopulmonary assessment practices across regions and income levels were noted. Respondents in North America and Europe reported using pulmonary function tests (PFTs) with diffusing capacity of the lungs for carbon monoxide (DLCO) more frequently than those in Latin America, or Asia/Africa (p < 0.001). The 6-min walk test (6MWT) was used less frequently by respondents in North America than other regions (p = 0.004). Use of oral corticosteroid and cyclophosphamide for treatment of JSSc varies significantly based on country income level, with higher usage in low- and middle-income nations. The scoping review identified 848 relevant articles for data extraction (ranging from 36 to 156 per domain) from a pool of 31,825 records, which were screened in multiple stages by 39 investigators. Conclusion We found significant variability in JSSc assessment and treatment preferences, influenced by geography and income. This highlights the urgent need for international collaboration and standardized approaches in JSSc care.